The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/md.0000000000012238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of co-infection by hepatitis C virus on immunological and virological response to antiretroviral therapy in HIV-positive patients

Abstract: We assessed the effect of co-infection by hepatitis C virus (HCV) on immunological and virological response at 48 weeks from initiation of antiretroviral therapy (ART).We included patients from the Cohort of Spanish HIV Research Network (CoRIS) starting ART between January 2004 and November 2014, had at least 1 CD4 T-cell count and viral load measurements both in the previous 6 months and at 48 (±12) weeks from ART initiation, and HCV serology before ART initiation. We used linear regression for mean differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…As estimated, up to 25% of HIV- infected population in the United States are also co-infected with HCV[8]. Co-infection with HCV and HIV has been associated with a faster progression of hepatitis and a higher liver-related mortality even in the era of antiretroviral therapy (ART)[9,10]. The exact role of HCV-infection in the natural history of HIV-infection is not clear.…”
Section: Hiv/hcv Co-infection Induced Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…As estimated, up to 25% of HIV- infected population in the United States are also co-infected with HCV[8]. Co-infection with HCV and HIV has been associated with a faster progression of hepatitis and a higher liver-related mortality even in the era of antiretroviral therapy (ART)[9,10]. The exact role of HCV-infection in the natural history of HIV-infection is not clear.…”
Section: Hiv/hcv Co-infection Induced Liver Injurymentioning
confidence: 99%
“…As reported, while HCV infection is not associated with an increase in AIDS-related events or deaths, co-infected individuals may have lower CD4 + T cell counts as compared to HIV-mono-infected patients[11,12]. In contrast, HIV co-infection produces numerous adverse effects by increasing replication of HCV[13], slowing down the HCV clearance, enhancing fibrogenesis[14] and decreasing the response to direct acting antiviral (DAA) treatment[10], ultimately increasing liver dysfunction and incidence of death. Eyster et al[15] compared the levels of HCV RNA before and after HIV-seroconversion in HCV-infected patients and reported that HCV RNA levels were enhanced 8-fold in patients co-infected with HIV compared to HCV mono-infected.…”
Section: Hiv/hcv Co-infection Induced Liver Injurymentioning
confidence: 99%
“…In addition, HCV treatment in PLWH is less effective [23,39]. The role of HCV as a co-factor in HIV disease progression remains controversial, but some studies have found lower absolute CD4+ cell counts and reduced immunological and virological responses after ART initiation [32,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…With the extended life expectancy offered by combined antiretroviral therapy, this patient subpopulation is at increased risk of long-term complications from HCV-associated chronic liver disease, including cirrhosis and hepatocellular carcinoma. The development of direct-acting antiviral agents (DAAs) has dramatically improved the treatment options for HCV, and a sustained virological response (SVR) in HIV/HCV coinfected patients is achieved at rates similar to those of HCV monoinfected patients [ 3 , 4 , 5 ]. However, outside of clinical trials, the population of HIV/HCV coinfected patients may have risk factors that, by themselves or in combination, may lead to lower SVR [ 6 ].…”
Section: Introductionmentioning
confidence: 99%